2022
DOI: 10.1002/ajs4.223
|View full text |Cite
|
Sign up to set email alerts
|

Beware the “loneliness gap”? Examining emerging inequalities and long‐term risks of loneliness and isolation emerging from COVID‐19

Abstract: Emerging evidence suggests COVID lockdowns have not only increased the social problem of loneliness but widened the ‘loneliness gap’ between the most and least lonely people. Qualitative investigation can reveal why this gap might have increased, for whom, and whether the loneliness gap will remain long term. Using multi‐wave qualitative survey data conducted during Australia’s 2020 lockdown period and beyond, we examine personal experiences of interaction transitioning out of lockdown. We find substantial and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 63 publications
0
7
0
1
Order By: Relevance
“…47 Studies hypothesize that this may be due, in part, to factors such as smaller social networks due to "pruning" during the pandemic and to postpandemic health-related social anxiety. 48 Addressing loneliness in the primary care setting is necessary because it provides an important point of contact for older adults, especially for those who are lonelyolder adults visit primary care between 5 and 6 times a year, on average, and those who are lonely average one additional visit per year. 49 Further, studies have found that older adults generally appreciate discussing social risks with their doctor 50 and report no discomfort with such screenings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…47 Studies hypothesize that this may be due, in part, to factors such as smaller social networks due to "pruning" during the pandemic and to postpandemic health-related social anxiety. 48 Addressing loneliness in the primary care setting is necessary because it provides an important point of contact for older adults, especially for those who are lonelyolder adults visit primary care between 5 and 6 times a year, on average, and those who are lonely average one additional visit per year. 49 Further, studies have found that older adults generally appreciate discussing social risks with their doctor 50 and report no discomfort with such screenings.…”
Section: Discussionmentioning
confidence: 99%
“…Feeling lonely in 2023 is now less common than during the height of the pandemic, but rates remain substantially higher than during pre‐pandemic times with over one third of older adults reporting loneliness as of January 2023 47 . Studies hypothesize that this may be due, in part, to factors such as smaller social networks due to “pruning” during the pandemic and to post‐pandemic health‐related social anxiety 48 …”
Section: Discussionmentioning
confidence: 99%
“…During the height of the pandemic, social isolation and loneliness increased for society at large 79–83 and for cancer survivors in particular 84 . Emerging research suggests that the negative social implications of the pandemic may be long‐lasting 85 . In one study conducted during the early stages of the pandemic, some YAs reported that increased social isolation enabled time for recovery, reflection, peace, and quiet 66 .…”
Section: Discussionmentioning
confidence: 99%
“…84 Emerging research suggests that the negative social implications of the pandemic may be longlasting. 85 In one study conducted during the early stages of the pandemic, some YAs reported that increased social isolation enabled time for recovery, reflection, peace, and quiet. 66 It is possible that the adjusted social expectations during this period may have reduced pressure to gather with friends and that the cancer experience was less isolating when more people, regardless of health status, were isolated.…”
Section: Meta-inferencesmentioning
confidence: 99%
“…Others included being male and having experienced stressful life events in the year prior to COVID-19, such as divorce or natural disaster or couples living with children, compared to those living without. Other research has reflected on the added pressures of parenting and home learning during COVID-19 and resulting social impairment and mental ill-health (Calear et al, 2022) and of adult children when pandemic-related job loss meant moving back home with ageing parents (Patulny & Bower, 2022). Although not examined explicitly, one can imagine such added responsibilities in living environment may impact one's resilience and control.…”
Section: Discussionmentioning
confidence: 99%